2020
DOI: 10.4155/bio-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Doping: Uses, Discovery and Validation

Abstract: A biomarker of doping indicates the biological response to the use of a prohibited substance or method. Uncovering novel biomarkers of doping is a key objective in order to improve antidoping outcomes such as the detection of doping and changing athlete behavior toward doping practices. While the antidoping field has been successful in validating novel metabolites of prohibited substances, there has been less success in developing new biomarkers of doping. Employing the most suitable study designs and analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Biomarkers for any diagnostics must be reliable, sensitive, specific, and discriminative. 39, 40 In addition, validation must determine predictability of unknown samples to correct state (i.e. Clean or Doped).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biomarkers for any diagnostics must be reliable, sensitive, specific, and discriminative. 39, 40 In addition, validation must determine predictability of unknown samples to correct state (i.e. Clean or Doped).…”
Section: Discussionmentioning
confidence: 99%
“…The present series of studies follows a general procedure for biomarker discovery and validation, 39, 40 including establishing robust baseline values by repeated sample collection at rest in all investigated groups, transports and storage conditions and routine procedures in accredited, clinical laboratories. Current approaches with multiplexing orthogonal biomarkers into one assay increase robustness to confounders and inter-laboratory variations, while reducing analytical costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benchmark and standard of the hematological module of the ABP are its capability of providing the anti‐doping experts with the information required for in‐depth blood profile interpretations, potentially also beyond the goal of uncovering practices commonly considered as blood doping as reported by Solheim et al in the context of testosterone ester administrations and the effect on markers of the ABP 188 . Strengthening and improving further the sensitivity and specificity of the ABP (also by including potential urinary biomarkers indicative for blood transfusions 189 ) is a continuous and, at the same time, intricate endeavor 190 . Here, in order to facilitate the identification of suspicious blood profiles for subsequent expert interpretation, Nunes et al suggested the implementation of a hematological perturbation index (HP Ix ) that assesses multivariate trends of blood parameters (as opposed to the current mathematical approach of univariate screening) and includes the variable of time intervals between sample collection sessions.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%